The African American experience in cyberspace : a resource guide to the best Websites on black culture and history - Alkalimat, Abdul (Pluto, 2004)
The World Wide Web is the greatest source of information used by students and teachers, media and library professionals, as well as the general public. There is so great a flow of information that it is necessary to have a tool for guiding one to the best and most reliable sources. This important new guide to the African American experience in cyberspace fills this need for people in all areas of Black Studies and Multiculturalism. There is no search engine list that can match the quality of sites to be found in this book. Alkalimat provides an easy to use directory to the very best websites that deal with the African American Experience. The first section covers every aspect of African American history, while a second section deals with a diverse set of topics covering society and culture. Each chapter has a brief essay, extensively annotation on the five best sites for each topic, and then a group of good sites and a short bibliography. This book is designed for a course at the high school or college level. This book should be kept near every home computer that people use to surf the web for Black content. Most people have found out that the major corporations and governments have been the dominant uploaders of information into cyberspace. This volume is different because it is a serious introduction to the full democratic use of the web. These websites will introduce people to the people who are serious about ending the digital divide because they are busy uploading information about the most excluded and marginalized people, the African American community. Many of these sites are being established by Black Studies academic programmes, as well as community based organizations and institutions.